Harmonic superspace from the AdS5 × S5 pure spinor formalism - Berkovits, Nathan [UNESP]; Fleury, Thiago [UNESP] (Springer Nature, 2013)
On-shell supergravity vertex operators in an AdS 5 × S 5 background are described in the pure spinor formalism by the zero mode cohomology of a BRST operator. After expanding the pure spinor BRST operator in terms of the AdS 5 radius variable, this cohomology is computed using $ \mathcal{N}=4 $ harmonic superspace variables and explicit super-field expressions are obtained for the behavior of supergravity vertex operators near the boundary of AdS 5. © 2013 SISSA, Trieste, Italy.
Keywords: AdS-CFT Correspondence; BRST Quantization; Superspaces